Modeling key performance indicators and resilience of elements with structural equation modeling approach - Elham Moghimi; Adel Azar; Mahmood Dehghan Nayeri (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Disruptions in the supply chain are abnormal events that have negative effects on the organization's performance. Since any disruption primarily affects organizational performance, one of the actions taken is to create and monitor key performance indicators. The use of appropriate indicators will reveal the areas that need more attention and care. The purpose of the current research is to provide a model for improving the key performance indicators with a resilience approach in the textile companies of Qazvin province by examining as much as possible the concept of supply chain resilience and the key indicators of organizational performance as well as the research conducted in this field.Methodology: This research is applied in terms of purpose, in terms of descriptive-correlation method and in terms of type, it is mixed (qualitative-quantitative). The initial research model was extracted from the literature and the final model was drawn in the qualitative stage through interviews with experts. The sampling method was targeted in the qualitative part and simple random sampling in the quantitative part. The statistical population of the research was 30 experts in the qualitative part and 300 senior staff-experts and managers of textile companies in Qazvin province in the quantitative part, of which 100 people were selected as a statistical sample. In order to collect research data, a 65-item questionnaire with a five-point Likert scale was used. Hypotheses were tested using the structural equation modeling method based on the Partial Least Square (PLS) method.Findings: The findings indicate that key performance indicators were effective in influencing organizational resilience as follows: customer indicators (0.155), financial indicators (0.416), employee indicators (0.171), marketing and sales indicators (0.188), social responsibility indicators (0.089), operational process and supply chain indicators (0.171).Originality/Value: In this research, the impact of key indicators of organizational performance on organizational resilience in textile companies is investigated.